Operational methods of HIV testing in emergency departments: a systematic review. - Haukoos, Jason S; White, Douglas A E; Lyons, Michael S; Hopkins, Emily; Calderon, Yvette; Kalish, Brian; Rothman, Richard E (Annals of emergency medicine, 2011)
Casual review of existing literature reveals a multitude of individualized approaches to emergency department (ED) HIV testing. Cataloging the operational options of each approach could assist translation by disseminating existing knowledge, endorsing variability as a means to address testing barriers, and laying a foundation for future work in the area of operational models and outcomes investigation. The objective of this study is to provide a detailed account of the various models and operational constructs that have been described for performing HIV testing in EDs.
Keywords: AIDS Serodiagnosis; Continuity of Patient Care; Counseling; Emergency Service, Hospital; HIV Infections; Humans; Informed Consent; Mass Screening